Protection system analysis on power distribution network - Oo, Htet Wai Yan (2017)
A well-planned and efficient distribution network is the important key to cope up with the highly increasing demand of electricity in domestic, industrial and commercial use. For the reliable power distribution network, the protection of the system is really important as short circuits occur due to the equipment insulation failure, system over-voltage caused by lighting or switching surges and other mechanical and natural causes. One of the main devices that are used in the power system protection is protective relay that sense the fault and trip the circuit break and protect the electrical equipment. Power can be recovered by taking from another alternate source of supply during fault to minimise the power failure. The main objective of this project is to study and analysis the current and time settings of protective relays and their coordination of time settings between circuit breaks for fault isolation. Different types of equipment in the distribution network such as power transformers; switch-gears and protection devices will be discussed to have a reliable distribution system in this project. Differential protection for transformers, over-current protection and the time current characteristic analysis for the relay will also going to be covered in this report. The main concept for the design project is to restore the electrical power from alternative supply after clearing the fault at the faulty transformer feeder. By using MATLAB Simulink software, to simulate the design project and produce waveform to analyse the voltage and current of the transformers when fault occurs at the distribution network.